De parias à victimes. Mobilisations féministes sur la prostitution en France et au Canada (1880-1920) - Yolande Cohen (Genre, Sexualité et Société)
The reglementation of prostitution in Europe was actively contested by abolitionists, while tolerance was met by temperance movements requiring its prohibition in North America. The comparative analysis of French and Canadian National Council of Women’s proposals show that they had an important influence in the adoption of reglementarist laws in both countries, reducing the distance between their legislations. By criticizing the double morals of the current laws on prostitution, the Councils legitimized women’s expertise on moral questions and contribute to integrate prostitutes in the law therefore transforming their status of “pariahs” into one of “victims (of male domination)”. Through a gendered activism, the Councils’s positions evolve from a “social purity” position to a more egalitarian one, asking for a unity of morals for both women and men, and for an international mobilization against women trafficking. In this paper, prostitution is shown to be one of the major battle fought by feminists of the first wave to establish equal protection of the law for women prostitutes.